Flattened cola improves high-intensity interval performance in competitive cyclists - Fowles, J. R.; O`Brien, M. W.; Comeau, K. G.; Thurston, B.; Petrie, H. J. (European Journal of Applied Physiology, 2021)
Purpose Some cyclists consume flattened cola during competitive events, but limited research has investigated if cola beverages elicit ergogenic effects, particularly on high-intensity exercise performance. Whether the potentially beneficial effects of cola are due to the caffeine and/or the carbohydrate content is also unclear. This study assessed the ergogenic effects of different cola beverages on performance during a constant power bout (CPB) and subsequent high-intensity interval efforts in competitive cyclists.